A logarithmic CMOS image sensor with wide output voltage swing range - De Souza Campos, Fernando [UNESP]; Da Silva, Marcelo Macchi; Bordon, Mario Eduardo [UNESP]; Swart, Jacobus W. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper presents logarithmic CMOS image sensor with wide output voltage swing range. Wide output voltage swing range is achieved by increasing the number of transistors connected as diodes of logarithmic CMOS image sensor. A prototype has been fabricated in 0.35μm AMS opto process. Four different pixels were fabricated using 20μmx20μm Nwel/Psub photodiodes with one, two, three and four transistors in series. The sensitivity measured were 136mV/Dec, 191mV/Dec, 281mV/Dec and 425mV/Dec for the pixels using one, two, three and four transistors in series respectively. This results shows that the sensitivity is increased by N approximately, were N is the number of transistors in series at pixels. Considering that the supply voltage the four-transistor pixel presents total output voltage swing range of 2.65V over a range of 120dB being the supply voltage 3.3V.
Keywords: CMOS; high sensitivity; logarithmic pixel; photodetector